2012
DOI: 10.1111/j.1547-5069.2012.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Workplace Spirituality and Organizational Citizenship Behavior Among Nurses Through Mediation of Affective Organizational Commitment

Abstract: This study illustrates that there are potential benefits owing to the positive influence of workplace spirituality on OCB and affective commitment among nurses. Managers of nursing services should consider workplace spirituality and its positive influence on nurses' outcomes in order to improve their performance and, subsequently, the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 29 publications
(45 reference statements)
10
96
1
2
Order By: Relevance
“…Second, this suggested that membership in an organization is either voluntary or defined, but social identity is a personal choice as results of their attitude towards their organization (Lewin, 1997in Goodman, 2002. Group members tend to identify themselves with their group (organization), when the group (organization) has a high profile, which contributes to high self-esteem (Cialdini, et al, 1976;Ellemers, et al, 1988in Goodman, 2002. In fact, local government institutions might not have contributed to improving selfesteem of the members.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this suggested that membership in an organization is either voluntary or defined, but social identity is a personal choice as results of their attitude towards their organization (Lewin, 1997in Goodman, 2002. Group members tend to identify themselves with their group (organization), when the group (organization) has a high profile, which contributes to high self-esteem (Cialdini, et al, 1976;Ellemers, et al, 1988in Goodman, 2002. In fact, local government institutions might not have contributed to improving selfesteem of the members.…”
Section: Discussionmentioning
confidence: 99%
“…Fry and Slocum (2008) argue that workplace spirituality can produce positive outcomes for employees (e.g., better health and psychological well-being) and the organization (e.g., employee commitment and greater productivity). Workplace spirituality is also found to have a positive influence on affective commitment among nurses and nurses' performance outcomes (Kazemipour, Mohamad Amin & Pourseidi 2012). Other studies demonstrating that workplace spirituality contributes to commitment and organizational performance include Milliman et al (1999);Benefiel (2003); Sanders, Hopkins and Geroy (2003); Garcia-Zamor (2003);and Rego et al (2007).…”
Section: Spirituality In the Workplace Organizationalmentioning
confidence: 93%
“…Workplace spirituality which involves employees' experience of finding ultimate meaning in work and sense of connectedness with organizational members (Gupta et al, 2013) began to be viewed as a new perspective towards understanding employee behavior including OCB and hence improve organizational performance. Among the limited studies that had examined the link between spirituality and OCB are those by (Nasurdin et al, 2013;Kazemipour et al, 2012) who found significant correlations between spirituality and OCB. Considering studies on the spirituality-OCB link is limited, this paper intends to propose a framework on the effect of workplace spirituality, as an individual resource, on OCB and the mediating role of work engagement using the work engagement model by Bakker and Demerouti (2008) and previous empirical literature.…”
Section: Background Of Studymentioning
confidence: 99%